Zawartość wybranych metali ciężkich w glebie i pędach Vaccinium myrtillus L. w Słowińskim Parku Narodowym - Parzych, Agnieszka (Leśne Prace Badawcze, 2014)
The research was carried out in the Słowiński National Park, in an area with 15 research stations in pine coniferous forests situtated at locations (1) inaccessible to tourists, (2) most frequently visted by tourists, as well as (3) in the vicintiy of parking lots. The analysed samples comprised surface generic levels (Ol, Ofh, A), above-ground material (shoots; leaves and stalks) and below-ground mateial (roots) of bilberry ( Vaccinium myrtillus ). The performed analyses showed statistically significant Spearman’s correlation coefficients for Zn content in the 'soil – stalk’ (r= -0,44, pZn>Cu.